Flexural behavior of double-skin steel tube beams filled with fiber-reinforced cementitious composite and strengthened with CFRP sheets - Al-Nini A.; Nikbakht E.; Syamsir A.; Shafiq N.; Mohammed B.S.; Al-Fakih A.; Al-Nini W.; Amran Y.H.M. (MDPI AG, 2023)
Beams and girders; Carbon fiber reinforced plastics; Composite structures; Filled polymers; High performance concrete; Reinforcement; Steel fibers; Tubular steel structures; Carbon fiber reinforced polymer; Concrete filled doubleskin steel tube (CFDST); Concrete-filled steel tubes; Fiber reinforced cementitious composite; Flexural behavior; Flexural stiffness; High performance fiber reinforced cementitious composites; High-performance fibers; Fiber reinforced concrete